Effect of botulinum toxin-A injection applied to the mentalis muscle on free gingival graft operation: A retrospective study - Sokmen, Kevser; Yildirim, Tuba Talo; Dundar, Serkan (Wiley, 2024)
Objective: The purpose of this retrospective study was to investigate the effects of Botulinum Toxin-A (BTX-A) injection into the mentalis muscle on the free gingival graft (FGG). Materials and Methods: Forty patients with keratinized gingiva insufficiency and Cairo's RT 2 gingival recession (formerly classified as Miller class III) in their mandibular central incisors were randomly divided into two groups: FGG and FGG + BTX. Plaque index (PI), gingival index (GI), probing pocket depth (PPD), keratinized gingiva width (KGW), attached gingiva width (AGW), clinical attachment level (CAL), gingival thickness (GT), gingival recession amount (GRA), gingival recession width (GRW), and root closure percentage (RCP%) parameters were measured at baseline and at first, third, and sixth months after the operation. Results: There was no difference in PI, GI, and PPD levels in both groups (p > 0.05). While the change in GT and RCP% levels were found to be statistically significantly higher at FGG + BTX group than FGG group, the change in GRW and CAL levels were statistically significantly lower (p < 0.05). Conclusion: The findings of this study indicate that BTX-A injection applied to the mentalis muscle after FGG operation may have positive effects in terms of KGW, AGW, GT, RCP%, GRW, and CAL parameters. Clinical Significance: As a result of the fact that BTX-A injection into the mentalis muscle contributed to the nutrition and immobility of FGG, positive developments were obtained in terms of clinical periodontal parameters. BTX-A injection into the mentalis muscle may be an alternative method that increases the success rate of Cairo's RT 2 gingival recession.
Keywords: botulinum toxin-A; free gingival graft; gingival recession; keratinized gingiva; mentalis muscle